(untitled) (Academicia Globe: Inderscience Research, 2021)
The article analyzes the research on investment, the positive impact of investment on economic development and its benefits.This article provides an econometric analysis of the impact of the volume of investments in the economy of Uzbekistan in 2000-2019 on the volume of GDP, the number of labor resources and the volume of money supply, and draws conclusions and recommendations based on the results of the study.